2019
DOI: 10.1055/a-0866-9427
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full-thickness transoral outlet reduction with semicircumferential endoscopic submucosal dissection

Abstract: Background Endoscopic full-thickness transoral outlet reduction (efTOR) is a therapeutic option to reduce a dilated gastrojejunal anastomosis (GJA) after Roux-en-Y gastric bypass (RYGB). Mucosal ablation with argon plasma coagulation (APC) is usually performed to achieve tissue adaptation. However, rupture of sutures before scarring can lead to recurrent dilatation of the GJA. Here, we describe efTOR with a semicircumferential endoscopic submucosal dissection (ESD-efTOR) as an alternative to APC-efTOR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Two studies 24 36 showed persistent weight loss and the rest of the studies demonstrated weight recidivism at 12 months. It is hypothesized that the weight loss post TORe was secondary to reduction in GJA size, improved eating habits, quicker gastric emptying times, and induction of satiety by stimulating gastric stretch receptors 11 24 27 28 . Weight recidivism was reported to be due to genetic factors, lack of dietary compliance, or due to suture breakage/migration leading to dilation of the GJA after TORe 26 27 28 36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies 24 36 showed persistent weight loss and the rest of the studies demonstrated weight recidivism at 12 months. It is hypothesized that the weight loss post TORe was secondary to reduction in GJA size, improved eating habits, quicker gastric emptying times, and induction of satiety by stimulating gastric stretch receptors 11 24 27 28 . Weight recidivism was reported to be due to genetic factors, lack of dietary compliance, or due to suture breakage/migration leading to dilation of the GJA after TORe 26 27 28 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Technical success of TORe procedure with full-thickness suturing device was defined in 7 studies. Four studies 12 23 24 25 considered post procedure GJA size < 10 mm and four studies 26 27 28 29 considered post-procedure GJA size < 12 mm to be technically successful.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all of the aforementioned patters, mucosal ablation with argon plasma coagulation on the gastric side of the GJA is typically performed in anticipation of suture placement. Furthermore, recent studies have suggested that adding endoscopic submucosal dissection before full-thickness suturing may achieve more durable results and greater reduction in GJA aperture [18,19]. There is also some evidence to support that reinforcement suturing in the distal pouch is important, whereas suturing in the pouch with the intention of reducing pouch volume may not be as important to achieve clinical success.…”
Section: Endoscopic Suturingmentioning
confidence: 99%